1968
DOI: 10.1136/jcp.21.6.729
|View full text |Cite
|
Sign up to set email alerts
|

Mycological tests and onychomycosis

Abstract: SYNOPSISThe value of direct microscopy and cultural tests in onychomycosis is reported on the results of the examination of 3,955 nail collections from patients infected with Trichophyton rubrum. Of the total number of mycological diagnoses, 15 % would have been missed if culture had been omitted and 53 % if direct microscopy had not been undertaken. METHODSIn the mycological diagnosis of onychomycosis tissue may be examined either by culture or by the so-called direct method, in which nail parings, after hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 4 publications
2
34
0
1
Order By: Relevance
“…As a "gold standard," KOH and culture is problematic: various studies have shown that 15 to 50% of the microscopy-positive nail specimens do not grow a culture (1,6,8,33). In our nail study (Table 2), the failure of culture was even more severe: a full 72.1% of PCR-confirmed dermatophytosis specimens (i.e., 109 of 151 specimens) did not yield the dermatophyte in culture.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As a "gold standard," KOH and culture is problematic: various studies have shown that 15 to 50% of the microscopy-positive nail specimens do not grow a culture (1,6,8,33). In our nail study (Table 2), the failure of culture was even more severe: a full 72.1% of PCR-confirmed dermatophytosis specimens (i.e., 109 of 151 specimens) did not yield the dermatophyte in culture.…”
Section: Discussionmentioning
confidence: 70%
“…These methods are low in specificity and may be very timeconsuming, because growth, sporulation, and routine physiological testing (e.g., urease enzyme assay) of the fungi involved may take 2 to 4 weeks. In addition, 15 to 50% of microscopically true-positive samples fail to grow a culture (8,33). Moreover, dermatophyte species show an unusual level of variation in the expression of phenotypic characteristics, e.g., the formation of pigments or conidia (46).…”
mentioning
confidence: 99%
“…It is always possible with mold infection, as with dermatophytosis, to sample fortuitously a portion of the lesion that is suboptimal for laboratory investigation, whether the area sampled contains effete inoculum, or whether it is marginal and is not yet heavily colonized. The laboratory study of dermatophytosis is constantly rendered difficult by the failure of truepositive samples to contain living inoculum in 15 to 25% of cases (4,6,7,13,32,34). In light of such possibilities, it may be unrealistic to expect low mold inoculum counts to be as readily interpretable as high counts are.…”
Section: Vol 39 2001 Diagnosis Of Nondermatophyte Mold Onychomycosimentioning
confidence: 99%
“…Thus, staining methods have a higher yield than culture techniques in these patients. 23 Our results showed that PATHPAS had the highest frequency of positive results (40 patients [63%]) in this sample population. This is lower than one would expect based on the clinical appearance of the nails in our patients.…”
Section: Commentmentioning
confidence: 56%
“…[25][26][27] The literature regarding evaluation of diagnostic tests for onychomycosis dates back to 1968. Davies 23 examined the frequency of positive results of KOH examination and culture for Trichophyton rubrum in 3955 patients for whom cultures had previously been positive for T rubrum onychomycosis. In that study, 46% of specimens showed positive culture or KOH examination.…”
Section: Commentmentioning
confidence: 99%